Analysis of the location of retinal lesions in central retinographies of patients with Type 2 diabetes. Issue 1 (30th August 2019) - Munuera‐Gifre, Eduardo; Saez, Marc; Juvinyà‐Canals, Dolors; Rodríguez‐Poncelas, Antonio; Barrot‐de‐la–Puente, Joan‐Francesc; Franch‐Nadal, Josep; Romero‐Aroca, Pere; Barceló, Maria Antonia; Coll‐de‐Tuero, Gabriel
Abstract: Purpose: To describe the distribution of Type 2 DM retinal lesions and determine whether it is symmetrical between the two eyes, is random or follows a certain pattern. Methods: Cross‐sectional study of Type 2 DM patients who had been referred for an outpatients' ophthalmology visit for diabetic retinopathy screening in primary health care. Retinal photographic images were taken using central projection non‐mydriatic retinography. The lesions under study were microaneurysms/haemorrhages, and hard and soft exudates. The lesions were placed numerically along the x‐ and y‐axes obtained, with the fovea as the origin. Results: From among the 94 patients included in the study, 4770 lesions were identified. The retinal lesions were not distributed randomly, but rather followed a determined pattern. The left eye exhibited more microaneurysms/haemorrhages and hard exudates of a greater density in the central retina than was found in the right eye. Furthermore, more cells containing lesions were found in the upper temporal quadrants, (especially in the left eye), and tended to be more central in the left eye than in the right, while the hard exudates were more central than the microaneurysms/haemorrhages. Conclusion: The distribution of DR lesions is neither homogeneous nor random but rather follows a determined pattern for both microaneurysms/haemorrhages and hard exudates. This distribution means that the areas of the retina most vulnerable to metabolic alteration can be identified. The results may be useful for automated DR detection algorithms and for determining the underlying vascular and non‐vascular physiopathological mechanisms that can explain these differences.